ANALISIS RETURN DAN RISIKO INVESTASI PADA REKSADANA SAHAM (Studi Pada Reksadana Saham yang terdaftar di Bursa Efek Indonesia Per.1.O1.2015-31.12.2017) - Shinta Maharani Trivena; Kartika Indah Permanasari; Oto Sunandar Dinata (Adbis: Jurnal Administrasi dan Bisnis, 2018)
This study is a research aimed to knowing the return and risk of investment in stock mutual funds. The population used is stock mutual funds listed on the Indonesia Stock Exchange Period January 1, 2015 to December 31, 2017. The sampleused purposive sampling, which is a sample based on spesific criteria, that is mutual funds in the form of Collective Investment contracts and stock mutual funds that are open during the period 1 January 2015-31 December 2017. The results of the study show the amount of return is comparableof the risk. Pratama Sahamare the highest returns during 2015, Simas Saham Bertumbuh provides the lowest risk in 2015, Sucorinvest Equity Fund is the bestfund in 2016 with the highest return and the lowest risk. The highest return for 2017 is held by Sucorinvest Equity Fund products, but the lowest risk is owned by Simas Saham Unggulan.